Quality of Life of Pregnant Women with Systemic Lupus Erythematosus - Rodrigues, Larissa; Costa, Maria Laura; Specian, Francisco Carlos; Sim-Sim, Maria Margarida Fialho; Surita, Fernanda Garanhani (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To assess the quality of life (QoL) of pregnant women with systemic lupus erythematosus (SLE) treated at a high-risk prenatal outpatient clinic during the third trimester of gestation.Methods An observational descriptive study was performed in a high-risk prenatal outpatient clinic. Women in the third trimester of pregnancy and undergoing antenatal care between July 2017 and July 2019 answered the abbreviated World Health Organization Quality of Life (WHOQOL-BREF) questionnaire, consisting of 26 questions divided into 4 domains (physical, psychological, social and environmental).Results We interviewed 50 pregnant women with a mean gestational age of 30 weeks (standard deviation [SD]: 10 weeks) who were diagnosed with SLE. The average age of the participants was 30 years (SD: 14.85), and the average time since the diagnosis of SLE was of 9.06 years (SD: 6.8 years). Most participants had a partner, did not plan their pregnancy (76%), and did not use contraception prior to pregnancy (80%). The score of each domain ranges from 0 (the worst score) to 100 (the best score). The means ±  SDs of the scores of the participants on each domain were: physical – 52.21 ±  18.44); psychological – 64.17 ±  18.56); social – 66.33 ±  27.09); and environmental – 64.56 (18.53). The means ±  SDs of the general QoL, and health-related QoL items were of 70.50 ±  24.06 and 70.00 ±  30.72 respectively.Conclusion The physical domain presented the lowest scores compared with the other three domains. Pregnant women with SLE had high overall QoL scores, and their health-related QoL scores were also relatively high.
Keywords: pregnancy; systemic lupus erythematosus; quality of life